Reframing Organizations / Artistry, Choice, and Leadership - Bolman Lee G.; Deal Terrence E (Jossey-Bass Publishers, 2003)
Making Sense of Organizations, The Structural Frame, Structures and Restructuring, The Human Resource Frame, Interpersonal and Group Dynamics, The Political Frame, The Manager as Politician, The Symbolic Frame, Organization as Theatre, Improving Leadership Practice, Reframing Leadership, Refraiming Ethics and Spirit, The Best Organizational Studies: Scholars' Hits and Popular Best Sellers.
Making Sense of Organizations, The Structural Frame, Structures and Restructuring, The Human Resource Frame, Interpersonal and Group Dynamics, The Political Frame, The Manager as Politician, The Symbolic Frame, Organization as Theatre, Improving Leadership Practice, Reframing Leadership, Refraiming Ethics and Spirit, The Best Organizational Studies: Scholars' Hits and Popular Best Sellers.